2010
DOI: 10.1007/s10661-010-1658-2
|View full text |Cite
|
Sign up to set email alerts
|

Trophic state index of a lake system using IRS (P6-LISS III) satellite imagery

Abstract: Water pollution has now become a major threat to the existence of living beings and water quality monitoring is an effective step towards the restoration of water quality. Lakes are versatile ecosystems and their eutrophication is a serious problem. Carlson Trophic State Index (CTSI) provides an insight into the trophic condition of a lake. CTSI has been modified for the study area and is used in this study. Satellite imagery analysis now plays a prominent role in the quick assessment of water quality in a vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 22 publications
1
38
0
1
Order By: Relevance
“…The rest of the stations indicated 'low degree of contamination' with mCd values from 1.52. These results are in agreement with previous results reported earlier that the Akkulam side of the lake is more polluted than Veli side (Sheela et al, 2010;Swarnalatha et al, 2013a). In this study it was found that 63.6% of observations in the Akkulam side recorded mCd > 1.5 indicating 'low degree of contamination' whereas only 33.3% of observations in Veli side were under 'low degree of contamination'.…”
Section: Assessment Of Degree Of Contaminationsupporting
confidence: 93%
“…The rest of the stations indicated 'low degree of contamination' with mCd values from 1.52. These results are in agreement with previous results reported earlier that the Akkulam side of the lake is more polluted than Veli side (Sheela et al, 2010;Swarnalatha et al, 2013a). In this study it was found that 63.6% of observations in the Akkulam side recorded mCd > 1.5 indicating 'low degree of contamination' whereas only 33.3% of observations in Veli side were under 'low degree of contamination'.…”
Section: Assessment Of Degree Of Contaminationsupporting
confidence: 93%
“…The Lake mouth remains open usually for 10 to 14 days, depending upon the influx of land drainage to the Lake. This episode repeats six to eight times a year [21].…”
Section: Introductionmentioning
confidence: 90%
“…Satellite imagery is georeferenced into WGS 84 coordinates, and resampled using the nearest neighbor. The water spread area of the AV Lake, is created using ERDAS [21]. The raw digital numbers of the imagery is converted into radiance using ERDAS Imagine 9.1.…”
Section: Processing Of Satellite Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…Técnicas convencionais de avaliação serão, em médio prazo, de difícil aplicação, dada a grande área conjunta ocupada pelos reservatórios em território brasileiro (NOVO & TUNDISI, 1988). Estudos têm demonstrado que o sensoriamento remoto pode ser usado tanto na estimativa de parâmetros individuais de qualidade da água (VENTURA, 2013) quanto na determinação do seu estado trófico (SAUSEN & PEREIRA, 1986;SHEELA et al, 2011). Eles já relataram a aplicabilidade das bandas TM1, TM2, TM3 e TM4 em estudos de parâmetros ambientais em ambientes aquáticos (LILLESAND et al, 1983;NOVO & TUNDISI, 1988;MITTENZWEY;GITELSON;KONDRATIEV, 1992;CHENG & LEI, 2001;WALDRON;STEEVES;FINN, 2001 Além disso, ações antrópicas vêm resultando em vários materiais que são carreados para o lago, como lixo urbano, restos de materiais de construção, partículas de asfalto liberadas das estradas, materiais orgânicos de fazendas e matas, agrotóxicos das áreas cultivadas e partículas de solo exposto e livre das estradas não pavimentadas (FRANZ et al, 2014).…”
Section: Pastoris (Esteves 2011)unclassified